Parallel processing of sensory inputs: an evoked potentials study in Parkinsonian patients implanted with thalamic stimulators - Insola, Angelo; Rossi, Simone; Mazzone, Paolo; Pasqualetti, Patrizio (Clinical neurophysiology, 1999)
In two drug-resistant Parkinsonian subjects, who underwent thalamic chronic stimulation for extrapyramidal symptoms relief, median nerve somatosensory evoked potentials (SEPs) were recorded before and at different times following the thalamic lead implant. In both subjects, a transient obliteration of post-rolandic SEPs components was detected; pre-rolandic waves' amplitude was preserved or showed a tendency to increase after the beginning of chronic stimulation. Parietal waves' amplitude totally recovered pre-surgical values after 1 month. Latency of both pre- and post-central components remained stable. The `dissociate behaviour' of the examined waves following the thalamic implant reinforces the hypothesis that short-latency sensory inputs are processed by separate and independent routes which are functionally segregated at subcortical level.